2019
DOI: 10.1016/j.chempr.2019.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Spherically Directed Synthesis and Enhanced Cellular Internalization of Metal-Crosslinked DNA Micelles

Abstract: We describe a facile and universal method that uses spherically directed reduction of metal ions for in situ crosslinking of DNA micelles. By combining characterization results and simulation algorithms, we achieved accurate structural profiling of DNA micelles for the first time. The metal-crosslinked DNA micelle, or MDM, combines the facile preparation and dense ligand distribution of a DNA micelle with the physical properties of DNA-metal-particle conjugates. As a result of the metal crosslink, the internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…83,84 Lyu et al designed a method for DNA micelle crosslinking in situ with the assistance of metal ions. 85 The monomer that makes up the micelle is formed by the covalent attachment of a single stranded DNA and a hydrophobic diacyl lipid. Specifically, the monomer consists of three parts, the most important of which is the part that acts as a template chain (Fig.…”
Section: Metal Ion-associated Crosslinking Methodsmentioning
confidence: 99%
“…83,84 Lyu et al designed a method for DNA micelle crosslinking in situ with the assistance of metal ions. 85 The monomer that makes up the micelle is formed by the covalent attachment of a single stranded DNA and a hydrophobic diacyl lipid. Specifically, the monomer consists of three parts, the most important of which is the part that acts as a template chain (Fig.…”
Section: Metal Ion-associated Crosslinking Methodsmentioning
confidence: 99%
“…Nevertheless, exotic materials would inevitably induce unwanted immune response, and up to date, the fate of the majority of man‐made polymers remains ambiguous yet . This dilemma inspires researchers to embark on the transport of metal ions using biomacromolecules coming from life systems, such as the recently highlighted proteins and genes . Unfortunately, these biomacromolecules fail to find their way to the targeted sites when in vivo administrated, leading to significant concerns, for example, systematic toxicity and drug tolerance of patients .…”
Section: Methodsmentioning
confidence: 99%
“…In terms of LONs, fast micelle formation was also able to prevent degradation by nuclease, possibly resulting from the steric hindrance of the DNA corona. Subsequent studies in the Tan group further improved the physical and biological stability of DNA–lipid micelles [ 46 48 ]. Our most recent study reported the introduction of a methacrylamide unit between the DNA and lipid segments, which served to cross link the amphiphiles after self-assembly via photoinduced polymerization (Fig.…”
Section: Design Of Lipid–oligonucleotide Probesmentioning
confidence: 99%